2012
DOI: 10.1158/0008-5472.can-12-0269
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Regulated Protein 78 Controls Cross-talk between Apoptosis and Autophagy to Determine Antiestrogen Responsiveness

Abstract: While more than 70% of breast cancers express estrogen receptor-α (ER+), endocrine therapies targeting these receptors often fail. The molecular mechanisms that underlie treatment resistance remain unclear. We investigated the potential role of glucose-regulated protein 78 (GRP78) in mediating estrogen resistance. Human breast tumors showed increased GRP78 expression when compared with normal breast tissues. However, GRP78 expression was reduced in ER+ breast tumors compared with HER2-amplifed or triple-negati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
196
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 138 publications
(213 citation statements)
references
References 39 publications
17
196
0
Order By: Relevance
“…Recent experimental results point to a potentially major role for GRP78, a key player in the unfolded protein response (UPR), in anti-oestrogen resistance [4]. Consistent with previous studies [5,6] that observed increased GRP78 expression in several human breast cancer cell lines, these results showed that knockdown of GRP78 in ICI-resistant cells re-sensitized the cells to ICI, which reduced proliferation due to increased apoptosis.…”
Section: Introductionsupporting
confidence: 86%
See 4 more Smart Citations
“…Recent experimental results point to a potentially major role for GRP78, a key player in the unfolded protein response (UPR), in anti-oestrogen resistance [4]. Consistent with previous studies [5,6] that observed increased GRP78 expression in several human breast cancer cell lines, these results showed that knockdown of GRP78 in ICI-resistant cells re-sensitized the cells to ICI, which reduced proliferation due to increased apoptosis.…”
Section: Introductionsupporting
confidence: 86%
“…Hence, we assume that GRP94 controls the UPR arms in the same way as GRP78, and modify the equations accordingly. We assume a constant level of GRP94 protein, ignoring its upregulation by EnR stress, since its enhanced expression under GRP78 knockdown does not relieve the stress, as discussed in Cook et al [4], and so its upregulation may not be significant.…”
Section: Unfolded Protein Response Modulementioning
confidence: 99%
See 3 more Smart Citations